2017
DOI: 10.1186/s12914-017-0114-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of, and barriers to the disclosure of HIV status to infected children and adolescents in a district of Ghana

Abstract: BackgroundGlobally there are about 3.3million children under the age of 15 years living with HIV. Of this number, 88% live in sub-Saharan Africa. In Ghana, an estimated 33,000 children were said to be living with the HIV infection in 2012. Lack of disclosure adversely affects the well-being of the child, including access to paediatric HIV treatment and care and adherence to treatment. However, the greatest psychosocial challenges that parents and caregivers of HIV-infected children face is disclosure of HIV st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
55
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 11 publications
9
55
6
Order By: Relevance
“…Evidence continues to grow of the negative relationship of stigma to pre‐exposure prophylaxis [1], HIV testing [2‐4], linkage and retention in care [5‐7], medication adherence [8‐13] and viral load suppression [2,14,15]. More visible global recognition of stigma in fuelling the HIV epidemic and in undermining the HIV response has been forthcoming through recent global declarations [29,35,71].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence continues to grow of the negative relationship of stigma to pre‐exposure prophylaxis [1], HIV testing [2‐4], linkage and retention in care [5‐7], medication adherence [8‐13] and viral load suppression [2,14,15]. More visible global recognition of stigma in fuelling the HIV epidemic and in undermining the HIV response has been forthcoming through recent global declarations [29,35,71].…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence documents that stigma undermines HIV prevention strategies such as pre‐exposure prophylaxis [1], HIV testing [2‐4], linkage to and retention in care [5‐7], medication adherence [8‐13] and ultimately viral load suppression [2,14,15]. Increasingly recognized as a key determinant of health and health inequity [16], stigma is a powerful social process characterized by labelling (distinguishing differences), stereotyping (attributing negative characteristics to the distinguished differences), separation (through physical and social isolation), leading to status loss (social and economic) and discrimination, all occurring in the context of power [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found that only 46.1% knew their HIV status at baseline, and 74.1% by 24 months of follow-up. Although this should be closer to 100% according to the WHO recommendations, this is higher than reported in previous studies, particularly for West Africa [25,31,42]. In Ghana, two separate studies reported the proportion of HIV disclosure to be 11.2% among children and adolescents aged 8-14 years in 2009 and 44% among ALHIV aged 12 -19 years in 2015 [25,43].…”
Section: Discussionmentioning
confidence: 61%
“…In many African pediatric sites, even if children or adolescents on ART, healthcare providers and caregivers delayed their HIV-disclosure because of cultural factors, the lack of national guidance [21]. Caregivers are also not ready, and fear their adolescent will disclose the family secret with subsequent stigma [25][26][27][28]. According to a previous review, 1.7% to 41% of children and ALHIV in low and middle-income countries are fully disclosed of their HIV-positive status [29].…”
Section: Introductionmentioning
confidence: 99%